2019
DOI: 10.1532/hsf.2197
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Microembolus and Plasma D-dimer in Evaluating the Warfarin Anticoagulant Therapy Efficacies for Patients with Atrial Fibrillation

Abstract: Background: To investigate the roles of microembolus and plasma D-dimer in evaluating the warfarin anticoagulant therapy efficacies for patients with atrial fibrillation (AF). Methods: Fifty-six AF patients were treated with aspirin antiplatelet therapy (Group ASP) and forty AF patients were treated with warfarin anticoagulant therapy (Group WAR). The microemboli and plasma D-dimer in these two groups were monitored and compared before and after treatment. Results: Group ASP had 21 and 17 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…16,17 Few domestic and international studies have been conducted in patients with persistent AF to assess the risk of embolism. [18][19][20] Previous research has suggested that D-d and LAD are both independent predictors of embolic risk in patients with AF. [5][6][7] According to our study, the CHA2DS2-VASc score, D-d level, and LAD were significantly higher in the positive group than in the control group.…”
mentioning
confidence: 99%
“…16,17 Few domestic and international studies have been conducted in patients with persistent AF to assess the risk of embolism. [18][19][20] Previous research has suggested that D-d and LAD are both independent predictors of embolic risk in patients with AF. [5][6][7] According to our study, the CHA2DS2-VASc score, D-d level, and LAD were significantly higher in the positive group than in the control group.…”
mentioning
confidence: 99%